Pengembangan E-Bahan Ajar Berbantuan Artificial Intelligence (AI) pada Pembelajaran Sejarah untuk Meningkatkan Hasil Belajar Siswa Kelas XI SMA Negeri 14 Padang - Ranthy Febrin Yolani; Rahmiyati Rahmiyati (YASIN, 2026)
The development of digital technology demands innovation in teaching materials for history learning, particularly because history learning is still often perceived as boring and has not been supported by teaching materials that are engaging and appropriate to the ability level of senior high school students. This study aimed to develop Artificial Intelligence (AI)-assisted E-Teaching Materials for history learning and to determine their feasibility, practicality, and effectiveness in supporting the learning outcomes of Grade XI students at SMA Negeri 14 Padang. This study used a Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects consisted of one learning resource expert lecturer, one content expert lecturer, two subject matter expert lecturers, one history teacher, and 120 Grade XI Phase F students. Data were collected through observation, interviews, and validation questionnaire sheets. The product developed was a digital E-Teaching Material that integrated history content, images, videos, and AI-assisted design through the Canva application. The results showed that the AI-assisted E-Teaching Materials were declared valid and feasible for use based on the assessments of the learning resource expert, content expert, and subject matter experts. The learning resource expert assessment obtained an average score of 3.4, the content expert 3.5, and the two subject matter experts a combined average score of 3.6. The practicality test results showed an average score of 4.0 from the teacher and 3.3 from the students, indicating that this teaching material was practical for use in learning. In addition, the product was considered effective and efficient in terms of place and space. Thus, AI-assisted E-Teaching Materials can serve as an innovation in history learning that supports the improvement of students’ interest and learning outcomes through the presentation of material that is more engaging, digital, and contextual.